Analysis of CFTR gene mutations and Cystic Fibrosis incidence in the Ecuatorian population. - Patricio Valle, Édison; Israel Burgos, Ramiro; Valle, José Rubén; Egas Béjar, Daniela; Ruiz-Cabezas, Juan Carlos (Investigación Clínica, 2009)
Ecuador is one of the Latin American countries where cystic fibrosis has not been thoroughly studied. The goal of this study was to establish the incidence of this specific pathology and the incidence of the 29 most common European CF mutations in EcuadorÂ´s population.We performed a prospective-descriptive study with the intention of including patients registered at the Ecuadorian Cystic Fibrosis Foundation as well as the main pediatric hospitals in Ecuador. The inclusion criteria were clinical manifestations of cystic fibrosis plus two positive pilocarpine iontophoresis sweat tests (CI > 60 mEq/L). We tested F508del mutation by heteroduplex method and then, we confirmed these results and searched for other 28 frequent European mutations aside from F508del by a reverse dot blot technique (INNO-LiPA CFTR 29 + Tn). Sixty two unrelated patients were included. Both heteroduplex and reverse dot blot methods identified 53.22% of all mutations. The estimated Ecuadorian cystic fibrosis incidence was 1:11,252. The mutations found and their incidence were F508del (37.1%), G85E (8.9%), G542X (2.4%), N1303K (2.4%), G551D (1.6%) and R334W (0.8%). The incidence of cystic fibrosis in Ecuador is closely similar to other Latin American countries where there is a large “mestizo” population. We are reporting one of the highest incidences of G85E in the world.